Presentation and Outcome of Infection in Hospitalized Patients with Diabetic Foot at a Tertiary Care Hospital - Zahid Miyan; Nazish Waris; Awn Bin Zafar; Uroosa Shafiq; Muhammad Saif Ulhaque; Muhammad Danish Muneeb; Bilal Tahir; Abdul Basit (Journal of Diabetology)
Abstract Background and Aim: To observe presentation and outcome of diabetic foot infection (DFI) in hospitalized patients at a tertiary care center. Materials and Methods: This prospective clinical study included all those patients who visited the out-patient department (OPD) of the foot clinic of Baqai Institute of Diabetology and Endocrinology and were admitted to the hospital due to DFI from August 2020 to April 2021. Patients with DFI were assessed and classified into mild, moderate, and severe infections according to the Infectious Disease Society of America (IDSA)/International Working Group On Diabetic Foot guideline protocol. Primary outcome was healing either without amputation, or with minor or major amputation. Results: A total of 2405 patients visited the OPD and 658 got admitted. Of these 211 patients with DFI were included. Males 158 (75%) were predominant. As per IDSA classification, 99 (46.9%) had severe infection, 94 (44.5%) had moderate, while 18 (8.53%) had mild infection. Overall, 150 (71.1%) infected Diabetic Foot Ulcers (DFUs), 67 (44.6%) and 65 (43.3%) DFUs with moderate infection and severe infection respectively were healed without any amputation. Conclusion: Infection was found to be the major cause of amputation in most patients with toe amputation being more common. Early referral of patients to the tertiary care unit and a multidisciplinary approach may help prevent DFI from major and minor amputations.